Effect of negative air ionization technology on microbial reduction of food-related microorganisms. (1st November 2022) - Baggio, Anna; Marino, Marilena; Maifreni, Michela
Abstract: Negative air ions (NAI) have been shown to have bactericidal effects on various microbial species. Different concentrations of NAI and ozone (10 6 -7x10 6 NAI cm- 3 s −1, 2.20 mg h-1 of ozone or 8 × 10 6 -2x10 7 NAI cm −3 s −1, 0.02 mg h −1 of ozone, respectively) were studied to determine whether the effect of these treatments on six food-related microorganisms was due to NAI or also to the ozone that forms. Bacillus subtilis, Escherichia coli, and Listeria monocytogene s showed a significantly microbial reduction after the treatments of NAI with a low concentration of ozone, while Pseudomonas fluorescens, Penicillium roqueforti, and Saccharomyces cerevisiae were affected mainly by NAI and higher ozone concentration. It should be noticed that the reduction of the pathogen L. monocytogenes has been 2.17 Log after 72 h treatment to NAI and low ozone concentration. The results proved that ions (NAI) contribute to microbial killing. However, the sensitivity of microbial species is different and depends on individual parameters of the different microorganisms. NAI technology with low ozone production can be rapid, green, and low-cost and it can represent an alternative to the use of chemicals for the sanitation of air and surfaces in the food sector in order to reduce microbial contamination. Highlights: Negative air ions and low ozone densities were essential for the microbial reduction. This technology affects the microbial viability of pathogenic and spoilage food microorganisms. The antimicrobial effect has been influenced by microbial species, temperature and exposure time. Ions generators properties influenced the antimicrobial activity. Ionization may be a promising technology to maintain microbial load control.